Epigenetics in formation, function, and failure of the endocrine pancreas - Maria L. Golson; Klaus H. Kaestner (Elsevier, 2017)
Background: Epigenetics, in the broadest sense, governs all aspects of the life of any multicellular organism, as it controls how differentiated cells arrive at their unique phenotype during development and differentiation, despite having a uniform (with some exceptions such as T-cells and germ cells) genetic make-up. The endocrine pancreas is no exception. Transcriptional regulators and epigenetic modifiers shape the differentiation of the five major endocrine cell types from their common precursor in the fetal pancreatic bud. Beyond their role in cell differentiation, interactions of the organism with the environment are also often encoded into permanent or semi-permanent epigenetic marks and affect cellular behavior and organismal health. Epigenetics is defined as any heritable - at least through one mitotic cell division - change in phenotype or trait that is not the result of a change in genomic DNA sequence, and it forms the basis that mediates the environmental impact on diabetes susceptibility and islet function. Scope of review: We will summarize the impact of epigenetic regulation on islet cell development, maturation, function, and pathophysiology. We will briefly recapitulate the major epigenetic marks and their relationship to gene activity, and outline novel strategies to employ targeted epigenetic modifications as a tool to improve islet cell function. Major conclusions: The improved understanding of the epigenetic underpinnings of islet cell differentiation, function and breakdown, as well as the development of innovative tools for their manipulation, is key to islet cell biology and the discovery of novel approaches to therapies for islet cell failure.